A note on the Sumudu transforms and differential equations - Eltayeb, Hassan; Kılıcman, Adem (Hikari, 2010)
In this work we introduce some relationship between Sumudu and Laplace transforms, further; for the comparison purpose, we apply both transforms to solve diﬀerential equations to see the diﬀerences and similari- ties. Finally, we provide some examples regarding to second order diﬀerential equations with non constant coeﬃcients as special case